Screening For Antibiotics of Marine Microorganisms from Xanthid Crab. - Nur 'Izzah Fateha, Md Zaher (Universiti Malaysia Sarawak, UNIMAS, 2010)
A study was carried out to isolate antibiotic producing microorganisms from xanthid crabs which were collected from Satang Island, Division of Kuching, Sarawak. Isolation procedure involved swabbing method on NA and PDA medium. Nine bacteria and four fungi were successfully isolated from xanthid crab. Preliminary screening for antibacterial activity was conducted using spot inoculation method for bacteria and agar overlay technique for fungi against Staphylococcus aureus, Salmonella typhi, Enterobacter aerogenes and Escherichia coli. Of the nine bacterial isolates obtained, five isolates (B1.4, B2.1, B2.3, B2.4 and B2.5) were positive against S. aureus, and S. typhi. Besides, three fungal isolates (B1.1, B1.4 and B2.1) showed antibacterial activity against all test bacteria. The positive isolates were subjected to a second antibacterial test by agar well method for bacteria and agar overlay technique for fungi. In second antibacterial test, four bacterial isolates (B1.4, B2.3, B2.4 and B2.5) and three fungal isolates (B1.1, B1.4 and B2.1) showed positive antibacterial activity. For antifungal test, B1.1 showed zone of inhibition against Fusarium sp., B1.4 and B2.1. Another two fungal isolates (B1.4 and B2.1) were inhibited by Fusarium sp. Moreover, five methanol extracts of bacterial and fungal isolates were tested for antibiotics activity by Kirby-Bauer disc-diffusion method. Findings revealed that two bacterial extracts (B2.4 and B2.5) showed positive inhibition against all test bacteria meanwhile, two fungal extracts (B1.4 and B2.1) have activity against S.aureus and none inhibition showed by B1.1. The highest diameter zone of inhibition was recorded against S.aureus (9mm) for fungal extract (B1.4). The fungal isolates were identified as Penicillium sp. (B1.4 and B2.1 meanwhile, B2.4 and B2.5 bacterial isolates were identified as Gram negative. The results indicate that the bacteria and fungi isolated from xanthid crabs produce potential antibacterial, antifungal and broad spectrum of antibiotics compounds.